the article: Penggunaan Media YouTube dalam Pembelajaran Bahasa Arab untuk Meningkatkan Maharah Istima' Santri Ma’had Tsurayya Malang - Arham, Ahmad; Al Anshory, Abdul Muntaqim; Hasaniyah, Nur (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
This study aims to analyze the effectiveness of using YouTube as a learning medium in improving listening skills (maharah istima’) among students at Ma’had Tsurayya. A descriptive qualitative approach was used to examine the role of teachers, learning strategies, and students’ perceptions of YouTube utilization. Data were collected through direct classroom observation and a review of relevant literature. The results of the study indicate that YouTube is effective in improving understanding and listening skills in Arabic due to its ease of access, variety of materials, and interactive audiovisual features. The advantages of YouTube include flexible learning times, engaging visualizations of materials, and the ability to repeat content as needed. However, its effectiveness heavily depends on the active role of teachers in providing additional explanations and guidance to avoid misunderstandings. Challenges include the speed of native speakers' pronunciation, limited vocabulary, and audio clarity. Solutions implemented include the use of dictionaries, repeated listening exercises, and integration with other learning strategies. تهدف هذه الدراسة إلى تحليل فعالية استخدام يوتيوب كوسيلة تعليمية في تحسين مهارة الاستماع لدى طلاب معهد تسرايا. تم استخدام النهج الوصفي النوعي لدراسة دور المعلمين واستراتيجيات التعلم وتصور الطلاب لاستخدام يوتيوب. تم جمع البيانات من خلال الملاحظة المباشرة في الفصل الدراسي ودراسة الأدبيات ذات الصلة. أظهرت نتائج البحث أن YouTube فعال في تحسين فهم ومهارات الاستماع للغة العربية بسبب سهولة الوصول إليه، وتنوع المواد، والميزات السمعية البصرية التفاعلية. تتمثل مزايا يوتيوب في مرونة وقت التعلم، وتصور المواد بشكل جذاب، والقدرة على تكرار المحتوى حسب الحاجة. ومع ذلك، فإن فعاليته تعتمد بشكل كبير على الدور النشط للمعلم في تقديم شرح إضافي وتوجيه لتجنب سوء الفهم. تشمل التحديات التي تواجهها سرعة نطق المتحدثين الأصليين، ومحدودية المفردات، ووضوح الصوت. وتشمل الحلول المطبقة استخدام القاموس، والتدريب المتكرر على الاستماع، والتكامل مع استراتيجيات التعلم الأخرى.